Antipruritic effect of pretreatment with topical capsaicin 8% on histamine‐ and cowhage‐evoked itch in healthy volunteers: a randomized, vehicle‐controlled, proof‐of‐concept trial. (9th June 2017) - Andersen, H.H.; Marker, J.B.; Hoeck, E.A.; Elberling, J.; Arendt‐Nielsen, L.
Summary: Background: Chronic itch is difficult to treat. Low‐concentration topical capsaicin (0·006–0·05%) has previously been applied in itch therapy but evidence on its efficacy is contradictory. Objectives: This vehicle‐controlled, double‐blinded study investigated the effect of topical capsaicin 8% after 1‐ and 24‐h application on evoked itch, neurogenic inflammation and itch‐associated dysaesthesia. Methods: Sixteen healthy volunteers (aged 22 ± 0·5 years, nine female) were treated with capsaicin for 1 h and 24 h, and vehicle for 24 h on each volar forearm. Subsequently, histamine (1%, administered prick test lancets) and cowhage (40–45 spicules) were applied to the pretreated areas. Evoked itch and pain intensities were recorded for 10 min using a visual analogue scale (0–10 cm), while sensitivity to touch‐evoked itch was evaluated using von Frey filaments before and after itch provocations. Neurogenic inflammation was assessed using perfusion imaging. Results: In the vehicle areas peak itch responses to histamine and cowhage were 4·67 ± 0·58 and 5·15 ± 0·71, respectively. Capsaicin pretreatment reduced peak itch responses to histamine and cowhage after 24‐h pretreatment to 1·41 ± 0·58 ( P = 0·003) and 0·81 ± 0·18, ( P < 0·001), respectively. Capsaicin pretreatment for 1 h reduced only cowhage‐induced itch ( P = 0·023). Furthermore, 24‐h capsaicin pretreatment abolished punctuate hyperknesis and lowered histamine‐induced neurogenic inflammation but did not affect weal reactions. Conclusions: Topical capsaicin 8% pretreatment for 24 h reduced histaminergic and nonhistaminergic itch by about 75%, while a significant reduction (≈60%) was achieved for only nonhistaminergic itch in a standard 1‐h treatment. Further investigations are needed to elucidate the clinical potential of high‐concentration capsaicin as an antipruritic. Abstract : What's already known about this topic? Topical low‐concentration (0·006–0·05%) capsaicin has previously been investigated and applied as an antipruritic, but there is contradictory evidence on its efficacy and its effect size is modest. High‐concentration topical capsaicin (8%) has recently been developed and approved for the treatment of peripheral neuropathic pain. What does this study add? Topical capsaicin 8% reduces both histaminergic and nonhistaminergic itch intensity by an average of about 75% and abolishes punctuate hyperknesis when applied for 24 h. A significant antipruritic effect of about 60% can be achieved for nonhistaminergic itch with a 1‐h treatment duration (standard application time). Respond to this article Plain language summary available online